Optimizing outpatient oncology consult workflow using time-driven activity-based costing: Efficiency and financial impacts. Issue 28 (1st October 2022) - Weng, Julius; Mesko, Shane; Das, Prajnan; Chronowski, Gregory; Lee, Percy; Choi, Seungtaek; Koong, Albert C.; French, Katy E.; Aloia, Thomas A.; Ehlers, Richard A.; Elrod-Joplin, Dorothy; Kerr, Ashley; et al.
Abstract : 9 Background: Clinical efficiency is a key component of value-based healthcare, patient satisfaction, staff burnout, and institutional operational capacity. The objective of this study was to identify clinic inefficiencies using time driven activity-based costing (TDABC) and evaluate the implementation of a new clinical workflow in high volume, outpatient radiation oncology clinics. Methods: We conducted an IRB-approved quality improvement study in the Gastrointestinal (GI), Genitourinary (GU), and Thoracic Radiation (TRO) Oncology departments at a large academic cancer center and four additional network sites (HALs). TDABC methodology was used to create process maps and optimize consult workflow. Patient encounter metrics were captured utilizing a real-time status function in the electronic medical record (Epic Systems). Anonymous patient satisfaction telephone surveys were administered to patients at the HALs. Hourly wages were determined based on 2021 U.S. Bureau of Labor Statistics. Pre- vs post-implementation metrics were compared using the Mann-Whitney U test. Results: Consult data for 1328 patients pre-intervention and 1234 post-intervention across all sections was included. Median overall cycle time was reduced by 21% in GI (19 min, p < 0.001), 18% in GU (16 min, p < 0.001), and 12% in HALs (9 min, p < 0.001). The median interval between rooming and being seen by the attending physician decreased by 13% in GI (7 min, p < 0.001), 16% in GU (9 min, p < 0.001), 21% in TRO (10 min, p < 0.001), and 9% in HALS (4 min, p < 0.005). For each consult, there was a median financial savings of 29 for GI, 24 for GU, 5 for TRO, and 14 for HALs per consult. From patient satisfaction surveys (95/177), 99% of patients reported their providers spent adequate time with them, 85% reported their appointment began on time, and 91% reported being seen by a care provider in a timely manner. Conclusions: TDABC is a successful method to identify opportunities to improve clinical efficiency. Implementing workflow changes based upon these findings led to substantial reduction in overall encounter cycle times and patient wait times across multiple departments. Furthermore, patient satisfaction was high and there were significant financial savings with the new workflow. These findings may also have implications for reducing staff burnout and expanding clinical capacity across the magnitude of clinical enterprise.Pre- vs post-implementation median cycle time and consult cost. Section Pre Cycle Time (min) Post Cycle Time (min) P-value Pre Cycle Time Cost Post Cycle Time Cost Savings per Consult GI 91 72 < 0.001 137.41 108.72 28.69 GU 89 73 < 0.001 134.39 110.23 24.16 TRO 72 69 0.10 108.72 104.19 4.53 League City 74 65 0.012 111.74 98.15 13.59 Sugarland 67 55 0.002 101.17 83.05 18.12 West Houston 77 71 0.20 116.27 107.21 9.06 Woodlands 88 73 < 0.001 132.88 110.23 22.65